Finance Digitalization and its impact on labour market - Mosteanu, Narcisa Roxana (Technium Social Sciences Journal, 2020)
Finance digital transformation has become the most commonly used words in the last decade. Enhancing the efficiency and the survival of institutions is related to the adoption of innovation of digital changes. Redesigning the organizational structure of any institution starts with employees and their skills and competencies. This article aims to show how the process of digitalization of the financial system and the adoption of new technologies have changed the approach of the workplace, the way of doing business and redefined the parameters of the financial products and services offered. The research presents the challenges faced by organizational design in the banking industry and how the structure of employees it is changed. Starting to form financial institutions cases and extrapolating to the labour market, in general, the paper underlines the movements of the job market and the possible solutions to redirect the specialization curriculums in order to equip people with those qualifications and skills which will make them employable on the current digitalized business environment.